Relationship Between Disease Characteristics and Oral Radiologic Findings in Systemic Sclerosis: Results From a Canadian Oral Health Study. Issue 5 (27th April 2016) - Baron, Murray; Hudson, Marie; Dagenais, Marie; M donald, David; Gyger, Geneviève; El Sayegh, Tarek; Pope, Janet; Fontaine, Audrey; Masetto, Ariel; Matthews, Debora; Sutton, Evelyn; Thie, Norman; et al.
Abstract : Objective: Systemic sclerosis (SSc; scleroderma) is associated with a wide periodontal ligament (PDL) and mandibular erosions. We investigated the clinical correlates of SSc with these radiologic abnormalities. Methods: Subjects from the Canadian Scleroderma Research Group cohort underwent detailed radiologic examinations. Associations between radiologic abnormalities and clinical manifestations of SSc were examined with univariate and multivariate analyses. Results: The study included 159 subjects; 90.6% were women, the mean ± SD age was 56 ± 10 years, diffuse disease was present in 28.3%, and mean ± SD disease duration was 13.7 ± 8.4 years. Widening of the PDL involving at least 1 tooth was present in 38% of subjects, and 14.5% had at least 1 site in the mandible with an erosion. In analyses adjusting for age, disease duration, sex, smoking, and education, we found significant associations between the number of teeth with widening of the PDL and disease severity assessed by the physician global assessment (PGA) (relative risk [RR] 1.19, 95% confidence interval [95% CI] 1.02–1.39, P = 0.028). Analyses replacing the PGA with the skin score, disease subset, or anti–topoisomerase I antibodies confirmed the relationship with indices of disease severity. There was no relationship between either the number of teeth with periodontal disease or the number of missing teeth, and the number of teeth with wide PDL. A smaller interdental distance (RR 0.89, 95% CI 0.82–0.97, P = 0.006), but not disease severity, facial skin score, or ischemia was associated with a larger number of erosions. Conclusion: In SSc, a wide PDL may reflect generalized overproduction of collagen, and mandibular erosions are related to local factors in the oral cavity.